Research on the History of Universities in Italy. A Historiographical Overview of the Last Century - Pomante, Luigiaurelio (CIAN-Revista de Historia de las Universidades, 2017)
This paper intends to reconstruct a history of the Italian university historiography of the last hundred years. Since the early attempts of the early twentieth century started in some of the oldest universities to create organisms for research and structures in higher education, the work retraces the most important stages of a process in which have progressively offer many opportunities for discussion between experts in this sector of the entire Peninsula. Since the nineties of the last century these researches have undoubtedly experienced a moment of particular flowering and renewal whose work gives ample account. On the basis of a considerable number of conferences organized in various Italian cities and a considerable amount of scientific production on the theme of higher education in Italy, will therefore analyze the most significant methodological and the mostrecent perspectives of research and identify new and interesting categories hermeneutical.
Keywords: history of the university; higher education; historiography; bibliography; Italy; XX-XXI Centuries